Optical absorption in LiF, LiF:Mg, LiF:Mg, Cu, P irradiated with high gamma and beta doses. (November 2017) - Remy, K.; Sholom, S.; Obryk, B.; McKeever, S.W.S.
Abstract: We examine the optical absorption spectra of a variety of LiF materials, variously doped with Mg, Cu and/or P. Both single crystal LiF (from various sources) and LiF:MCP-N sintered pellets are examined. We follow the growth of the individual absorption bands as a function of high, gamma-photon doses and high, beta-particle doses. Detailed deconvolution of the spectra, measured at room temperature following irradiation also at room temperature, allows for the behavior of the individual OA peaks to be analyzed. We also examine the post-irradiation step annealing of the spectrum by progressively heating the samples to high temperatures. We compare the data so obtained with the shape of the thermoluminescence glow curve recorded from these same materials. F, F 2, F 3, F 3 +, F 3 − and F 4 centers are identified, along with impurity-related and possible Li-colloid absorption features. The various OA bands grow with dose (1 kGy–700 kGy) and the annealing behaviors of the various absorption features are discussed. Highlights: Optical absorption in LiF:Mg, Cu, P and related materials following high dose. Change in absorption spectra as a result of post-irradiation annealing. Relevance to high-dose thermoluminescence.